2021
DOI: 10.22541/au.161366874.40196343/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of Clinical Characteristics and Outcomes of Postoperative Infections in Living Liver Donors

Abstract: Aim: To analyze developing infections after living donor hepatectomy (LDH) in living liver donors (LLDs). Methods: Demographic and clinical charecteristics of 1106 LLDs were retrospectively analysed in terms of whether postoperative infection development. Therefore, LLDs were divided into two group: with (n=190) and without (n=916) antimicrobial agent use. Results: The median age was 29.5 (min-max: 18-55). A total of 257 (23.2%) infection attacks (min-max: 1-8) was developed in 190 (17.2%) LLDs. The patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…After review of the titles and abstracts, 57 studies were selected 18–73 . The main features of the studies are reported in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After review of the titles and abstracts, 57 studies were selected 18–73 . The main features of the studies are reported in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The first outcome was the rate of overall complication, 15 20 , 23 , 24 , 33 , 35 , 48 , 47 , 52 , 59 , 61 , 64 , 68 , 71 , 72 , 73 comparative studies and 10 25 , 28 , 36 , 43 , 45 , 56 , 58 , 60 , 69 , 70 non‐comparative studies were included in the assessment of the QOE. The effect from comparative studies was lower with few events.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations